CHRONIC CONSTIPATION IN CHILDREN - E.G. Tsymbalova ("Paediatrician" Publishers LLC, 2011)
The article discusses questions of classification, anatomic and physiological peculiarities and pathogenetic aspects of chronic constipations forming in children. The problems of diagnostics of chronic constipation and its treatment with spasmolytics are analyzed.Key words: children, chronic constipation, diagnostics, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (2): 173-179)